Desenvolvimento rural e gênero: a participação das mulheres na organização de um movimento social o caso da Crabi PR. - Makoski-lombardi, Sheila Priscila (2006)
This paper aims to understand contributing measurements of women participation in organizing and managing a social movement - Crabi - to alter gender relation, traditionally existed in the field as well as gender segregation at work, family structure, and in main production activity definition taken as plural activities. Thus, this paper exams Cabri's social movement construction process as well as "women's center" that also represents a social movement, since women reach for support in the center to better understand their position in society as well as in the family. Through the evaluation of such process, we attempted to analyze work relevance, on the eye of the gender, and understand how relations are perceived in the Crabi movement. Thus, this paper is based on new social movement theories, among them the feminist movement and gender relation problematic, inserting these notions into the notion of family agricultural production and plural activity to understand the factors that lead to the development of this phenomenon. From this study, research results show that women participation in the social movement contributes positively in the social and economical structure of the studied families.